Morpheme-Based Reading and Writing in Spanish Children with Dyslexia - Suárez-Coalla, Paz; Martínez-García, Cristina; Cuetos, Fernando (Frontiers in Psychology, 2017)
It has been well documented that morphemic structure (roots and affixes) have an impact in reading, but effects seem to depend on the reading experience of readers and lexical characteristics of the stimuli. Specifically, it has been reported that morphemes constitute reading units for developing readers and children with dyslexia when they encounter a new word. In addition, recent studies have stated that the effect of morphology is also present in spelling, as morphological information facilitates spelling accuracy and influences handwriting times. The goal of this study was to investigate the role of morphology in reading and spelling fluency in Spanish children with dyslexia. For that purpose, a group of 24 children with dyslexia was compared with an age-matched group of 24 children without reading disabilities in performing a word naming task and a spelling-to-dictation task of isolated words. Morphological condition (high frequency base, low frequency base, simple) and lexicality (words vs. pseudowords) were manipulated. We considered, for the naming task, reading latencies, reading durations, reading critical segment (three first phonemes) durations and naming accuracy; and, for the spelling task, written latencies, writing durations for the whole word, writing critical segment (three first letters) durations and spelling accuracy. Results showed that Spanish children (with and without dyslexia) benefit from a high frequency base to initiate reading and writing responses, showing that they are familiar with the letter chunks that constitute a morpheme. In addition, base frequency impacts reading critical segment duration only for children with dyslexia, but for both groups in writing. In summary, children with dyslexia benefit from a high frequency base to read and spell unfamiliar stimuli.